PLASTIC WASTE AND ITS NEGATIVE IMPACT ON THE ENVIRONMENT - ORTIQOV ABDULLOX SHOVKATOVICH (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Plastic waste has become one of the most pressing global environmental problems. The excessive use of single-use plastics, such as bags, bottles, and packaging, has led to serious soil, air, and water pollution. Since plastics are non-biodegradable, they persist in the environment for hundreds of years, causing long-term ecological damage. One of the greatest concerns is microplastics, which accumulate in marine ecosystems, enter the food chain, and threaten both biodiversity and human health. Plastic waste also disrupts agricultural land fertility and contributes to climate change through improper incineration. Effective solutions include recycling systems, production of biodegradable materials, and public awareness campaigns. Reducing plastic consumption is crucial for ensuring a sustainable and healthy environment for future generations.